Mode choice for the journey to work during morning peak hour in Klang, Malaysia - A.F., Mohd Sadullah; Nur Fahriza, M. A.; A., Zulkiple (Centre for Advanced Research on Energy, 2018)
This research presents the evaluation of trigger levels at the equilibrium condition which users’ mode choice is equal for both private vehicles and public transport. The new Park and Ride at the Klang Komuter Station will attract more private vehicles users. This study chose travel time as an important factor in triggering users’ mode choice either to choose public transport or private vehicles during morning peak hour. The surveys performed are Origin-Destination Survey and Travel Time Survey. The trigger levels were evaluated by using Graphical Analysis. The result shows that the travel time for Bus Sample 4 and Bus Sample 5 are perfectly equal to the travel time of car. The perfectly equal of travel time for both private and public transport is expected to increase the number of public transport users and reducing the massive private vehicles on the road